THE VARIATION IN THE STRUCTURE OF ERYTHROCYTE NUCLEI WITH FIXATION - Davies, Howard G. (The Rockefeller University Press, 1962)
Observations have been made on the role of a divalent cation (calcium ion) during OsO(4) fixation of nuclei of frog erythrocytes, mainly after isolation from cells. The volume of the nucleus depends partly on the molecular interaction of charged macromolecules, is controlled by the ionic strength of the medium, and hence may be used as a guide in attempts to preserve structure. When the isolation and fixation media contain 0.01 M calcium at pH 6.3 the volume changes, in the light microscope, during processing are small. When the fixative does not contain these ions, reversible volume changes occur during fixation and dehydration. The chromatin of nuclei processed with minimal volume change appears, in the electron microscope, to contain fine dots and lines about 20 to 40 A in diameter, relatively close together. The chromatin structure of nuclei in which volume changes have occurred consists of dense irregularly shaped patches, relatively far apart, and ranging in diameter from about 200 A down to the limits of visibility (20 to 30 A). It is suggested that the latter structure is a precipitation artefact.